Congestion Tolls for Commercial Airports - Park, Rolla Edward (Econometrica, 1971)
This paper discusses the role of congestion tolls in increasing the efficiency of use of commercial airports, in terms of a simple model of air transportation. In contrast to previous discussions, users and producers of transportation service (passengers and airlines) are explicity distinguished. In the first version of the model, ticket prices are assumed-unrealistically-to be flexible and competitively determined; then perfect optimality is attainable by imposing an appropriate toll either on airlines or on passengers. In the more realistic second version of the model, ticket price is based above the competitive level. In the absence of a toll, there are two inefficiences: the level of transportation is non-optimal, and it is produced inefficiently, using partially loaded airplanes. An appropriate toll on airlines can do much to correct both of these inefficiencies, and is always superior to the best toll or passengers.